Investigating Cognitive Processes in Foreign Language Learning: Use of Introspective Measures (Revue El-Wahat pour les Recherches et les Etudes, 2020)
Findings in foreign language research are dependent on the data elicitation measures that the researcher selects in order to answer the target research questions. The present article provides a detailed account of the different introspective measures that researchers commonly opt for to collect data about learners’ learning processes, which are unobservable. The focus will be placed on various methods, like verbal reports and stimulated recalls. In addition to describing the procedures for every elicitation measure, the researcher reviews some of the studies that used such tools.  The aim is to provide researchers with some insights into how effectively they can have access to learners’ internal thought processes. This will help in adjusting teaching practices according to learners’ needs.Key words- research, cognitive, foreign, learners, introspection